Couple satisfaction and impact of confinement by COVID-19 pandemic in Mexico - Quezada-Berumen, Lucía del Carmen (2020)
Background: The aim of the study was to evaluate the relationship between marital satisfaction, measured by the Relationship Assessment Scale and the perceived impact of confinement due to COVID-19 in different areas of people’s lives, in a Mexican sample. Method: 101 people living as a couple, with an average age of 41.2 years (SD = 10.7), 54.5% women and 45.5% men were evaluated. Results: The main result was a negative and significant correlation that indicates that the greater the satisfaction in the relationship, the less impact of confinement in the areas of tranquility, happiness, health, physical condition and emotional well-being. Conclusion: The people with higher marital satisfaction will perceive less impact during the contingency by COVID-19 in the different areas of the person's life.